Potential of neutrino telescopes to detect quantum gravity-induced decoherence in the presence of dark fermions - Domi, Alba; Eberl, Thomas; Hellmann, Dominik; Krieg, Sara; Päs, Heinrich (Journal of Cosmology and Astroparticle Physics, 2025)
We assess the potential of neutrino telescopes to discover quantum-gravity-induced decoherence effects modeled in the open-quantum system framework and with arbitrary numbers of active and dark fermion generations, such as particle dark matter or sterile neutrinos. The expected damping of neutrino flavor oscillation probabilities as a function of energy and propagation length thus encodes information about quantum gravity effects and the fermion generation multiplicity in the dark sector. We employ a public Monte-Carlo dataset provided by the IceCube Collaboration to model the detector response and estimate the sensitivity of IceCube to oscillation effects in atmospheric neutrinos induced by the presented model. Our findings confirm the potential of very-large-volume neutrino telescopes to test this class of models and indicate higher sensitivities for increasing numbers of dark fermions.
CRIS-Team Scopus Importer:2025-04-25
Keywords: neutrino experiments; neutrinos; quantum black holes; solar and atmospheric neutrinos; ultra high energy photons